2021
DOI: 10.1016/j.jbc.2021.100684
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the catalytic domain of botulinum neurotoxin subtype A3

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The current study sought to establish how the previously identified LHD (268-357) mediated LC/A1 association with the plasma membrane [35]. A co-crystal of LC/A1 bound to SNAP-25 (residues 146-204 (PDB: 1XTG)) and the recently solved crystal structure of LC/A3 [43] showed the LHD to be organized into three sequential structural regions (R1-R3 (Figure 1). R1, residues 275-300, included an α-helix; R2, residues 302-334, included a loop, α-helix, and loop; and R3, residues 335-357, included an α-helix, loop, and α-helix.…”
Section: Structural Analysis Of the Low Homology Domain Of Lc/a1 Reve...mentioning
confidence: 93%
“…The current study sought to establish how the previously identified LHD (268-357) mediated LC/A1 association with the plasma membrane [35]. A co-crystal of LC/A1 bound to SNAP-25 (residues 146-204 (PDB: 1XTG)) and the recently solved crystal structure of LC/A3 [43] showed the LHD to be organized into three sequential structural regions (R1-R3 (Figure 1). R1, residues 275-300, included an α-helix; R2, residues 302-334, included a loop, α-helix, and loop; and R3, residues 335-357, included an α-helix, loop, and α-helix.…”
Section: Structural Analysis Of the Low Homology Domain Of Lc/a1 Reve...mentioning
confidence: 93%
“…Protein expression and purification were performed as described previously 66 . Proteins were expressed in E. coli strain BL21(DE3) (NEB).…”
Section: Methodsmentioning
confidence: 99%
“…Within N, A1 and A2 were identical, while A3LM possessed a unique K 11 R substitution. Within the LHD, A1 and A2 were 97% identical, while A3LM had ~60% primary amino acid homology with A1 and A2, with differences in surface charge potential as there is a cluster of basic amino acids present in A3LM that are absent in A1 [31]. Supporting roles for the N and LHD in intracellular LC targeting, such as A1 ectopically expressing A2 at steady state, were localized to the plasma membrane (Supplemental Figure S1, see Supplementary Materials). )…”
Section: Properties Of A1 and A3mentioning
confidence: 96%
“…Supporting roles for the N and LHD in intracellular LC targeting, such as A1 ectopically expressing A2 at steady state, were localized to the plasma membrane (Supplemental Figure S1, see Supplementary Materials). ) and middle A3LM (PDB: 7DVL) [31] and right A1 and A3LM merged with N (residues 1-17, red) and LHD (268-357, green) highlighted. Merge of A1 and A3LM was prepared with PyMol software.…”
Section: Properties Of A1 and A3mentioning
confidence: 99%
See 1 more Smart Citation